A Grammatical Errors Analysis in Students’ Comparison and Contrast Paragraph Writing - Erviana, Ridha Ikhva; Kurniasih, Veny (Universitas Pamulang, 2024)
This research focuses on analyzing grammatical errors in comparison and contrast paragraphs written by second-semester students of the English Department at Universitas Pamulang. Grammatical errors often occur in students' writing when the grammatical arrangement does not follow grammar rules. The main purposes of the research were to identify the types of grammatical errors and to describe the most frequent types of grammatical errors found in students' writing of comparison and contrast paragraphs. This research was carried out from October 2023 to June 2024 and used a qualitative descriptive research design. The subjects of the research were the twenty comparison and contrast paragraphs written by the students as a writing assignment. The data were collected from the original students' writing products, and the data were observed to find grammatical errors and classify the types of errors. Furthermore, the most frequent type of grammatical error was also calculated. The researcher analyzed the types of grammatical errors in students' writing based on Dulay, Burt, and Krashen's theory. The results showed that there were 127 grammatical errors, which were classified into 47 omission errors, 35 addition errors, 30 misformation errors, and 15 misordering errors. Additionally, the most frequent type of grammatical error was omission errors, which accounted for 37% of the total errors and had the highest percentage. The results of this research have implications for understanding strategies to address students' grammatical problems when they are producing text.